Peran Diaspora Armenia dalam Konflik Nagorno Karabakh Tahun 2020-2022 - Ramadhannil Yusuf; Hesti Rosdiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The Nagorno-Karabakh conflict from 2020 to 2022 highlights the significant role of the Armenian diaspora in supporting Armenia across various dimensions. The research aims to determine the extent to which the Armenian diaspora's support influences the Armenian government's capacity to handle the conflict. The study utilizes theories of public diplomacy and diaspora engagement, employing a mixed-methods approach that includes qualitative data from secondary data processing such as journals and written results containing data about Armenian Diaspora, official website of the Armenian government, and quantitative data from financial contributions and diplomatic records. Findings indicate that the Armenian diaspora's political lobbying and advocacy efforts have secured significant diplomatic support, while economically providing substantial remittances, investments, and humanitarian aid. Socially, the diaspora has shaped international public opinion through campaigns and cultural activities, and intellectually, it has offered strategic insights enhancing the government's approach to the conflict. Additionally, the mobilization of human resources by the diaspora has provided direct assistance in Armenia. This research offers a comprehensive understanding of the dynamics between the Armenian diaspora and the Armenian government, demonstrating the substantial impact of multidimensional diaspora support on the government's capacity to manage the Nagorno-Karabakh conflict.